The Relationship between Teachers' Professional Development and Academic Performance with Emphasis on the Mediating Role of Secondary School Boys' Bonding - Jafar Amiri (Institute of Management fekrenoandish, 2021)
Extended Abstract Abstract The aim of this study was to investigate the relationship between teachers' professional development and academic performance with emphasis on the mediating role of link with students' school. The research method was descriptive-correlation. The statistical population of the study was teachers and high school male students in Shiraz. 250 teachers were selected based on Krejcie and Morgan table by simple random sampling method and 213 students were selected by cluster random sampling method as a statistical sample. In the present study, the Pham and Taylor (1999) Academic Performance Questionnaire, Ayubi Avaz et al. (2015) and the link with Rezaei Sharif et al. (2014) were used, the validity of which was confirmed by academic experts and their reliability also, through Cronbach's alpha coefficient test, 0.85, 0.89 and 0.79 were obtained and confirmed, respectively. In order to analyze the data, structural equation technique was applied using Lisrel statistical software and Spss26 statistical software. Quantitative findings of the research hypothesis test showed that there is a positive and significant relationship between teachers' professional development and students' academic performance linked with school. There is a positive and significant relationship between students' connection with school and their academic performance and the connection with school has played a mediating role in the relationship between teachers' professional development and students' academic performance. Introduction The progress of any country is inextricably linked with the development of its human resources. Although there is no precise agreement among experts on the word progress and its exact meaning, the development of a country is one of the main goals of politicians, which is not possible without the development of skilled manpower. Training of human resources is also formed in schools at first, so identifying the factors that improve students' academic performance is a priority (Sayadpour and Sayadpour, 2018) .Studies have shown that a weak link with the school is accompanied with low academic achievement, Absenteeism, dropouts, peer conflicts, and behavioral problems. On the other hand, high levels of school affiliation are associated with positive outcomes such as academic achievement, increased academic motivation, self-efficacy and high grades, and academic achievement (sheikholeslami and etal , 2018). Therefore, understanding the process of changes in connection with school, its causes and consequences can help researchers in school-based interventions. In other words, the importance of paying attention to the issue of school connection arises from the student's perception of school has important implications for their behavior in and out of school. It is worth noting, however, that the student's connection to the school is an important issue at all levels of education; this issue is very important in adolescence; so that over the past two decades, educators and school health professionals have increasingly emphasized that attachment to school is an important factor in reducing the risk of adolescents engaging in risky behaviors. Connection with school can be Defined as the level of students' satisfaction with being at school; relationship with the school as students' perception of school support that has a favorable atmosphere and a supportive culture (Waters and Cross, 2010). Considering the importance of professional development and connection with school in improving students' academic performance, recognizing the affective factors of it is one of the main necessities of our country's educational system. To this end, this study examines the question of whether there is a relationship between teachers' professional development and academic performance by emphasizing the mediating role of bonding with the school of high school male students? Case study In this study, all teachers and male high school students in Shiraz were engaged in employment and education; Has been examined as a case study. Theoretical framework Research on the relationship between professional development variables and academic performance has shown that there is a significant relationship between teachers' professional abilities and students' academic performance (Mohajeri and etal, 2012). In a qualitative study, the needs and methods of professional development of school principals were presented. These subjects included educational leadership, management and organizational leadership, ethical leadership, social participation and technology (Hayat and etal, 2015). Pourkarimi and Ramezanpour (1398) in a qualitative study showed that for the professional development of e-learning, faculty members should pay attention to the 5 main dimensions: knowledge development, skill development, ability development, attitude development and feature development (Pourkarimi and Ramezanpour, 2019). In another study, it was shown that there is a relationship between school connection and academic achievement as well as participation in extracurricular activities of students (Howard and Ziomek, 2009). In a meta-analysis, it was shown that there is a significant correlation between school connection and academic achievement and academic performance (Korpershoek and et. al, 2020). Methodology This research is of descriptive-correlation type. The study population includes all teachers (721 people) and male high school students in Shiraz (2726 people). To determine the sample size of the first part of the statistical population (teachers), Krejcie and Morgan table was used and 250 people were selected as a sample size, by simple random sampling. The sample size of students was done by cluster random sampling method. Based on this, three schools were randomly selected and one class was selected from each school, which includes the tenth to twelfth grade classes. A total of nine classrooms were selected with a student body of 213 students. To collect data, standard questionnaires of academic performance of Pham and Taylor (1999), professional development of Ayoubi Avaz et al. (2015) and link with Rezaei Sharif et al. (2014) are used. Discussion and Results After testing the measurement models, it is necessary to provide a structural model that shows the relationship between the latent variables of the research. All the research hypotheses had a good fit. Also, for investigating the mediating effect of the link with the school, the direct effect of the two structures with the indirect effect in the case of involving the variable of the link with the school should be examined in order for the mediator with the school connection to be considered acceptable when the effect incteases. In the present hypothesis, the power of the direct relationship between professional development and academic performance is (0.41). The indirect effect if there is a mediator variable of school connection is:  (0.51) = (0.78) * (0.66) Due to the lower effect of direct path compared to indirect paths, therefore, the existence of the mediator variable of school connection increases the strength of the relationship and the mediating role of school link is confirmed in the present hypothesis. Conclusion The results of the first hypothesis of the research showed that there is a positive and significant relationship between teachers 'professional development and the connection with students' school. This hypothesis is explained in such a way that the professional development and increasing of the knowledge and skills of teachers is necessary for the success of efforts in the field of education improvement (Mohamadi and Hasani, 2019). Increasing teachers' ability to communicate with students can stimulate students' willingness to attend at school and prepare them to take lessons in the classroom (Kyndt and etal, 2016). These results are consistent with and supported by the findings of Jafary et al. (2017). Based on this, the first hypothesis of the research is also confirmed. The results of the second hypothesis of the research showed that there is a positive and significant relationship between students' connection with school and their academic performance.